Alpha-lipoic acid alleviates colistin nephrotoxicity in rats. (May 2021) - Oktan, Mehmet Asi; Heybeli, Cihan; Ural, Cemre; Kocak, Ayse; Bilici, Gokcen; Cavdar, Zahide; Ozbal, Seda; Arslan, Sevki; Yilmaz, Osman; Cavdar, Caner
Colistin methanesulfonate (CMS), a clinical form of colistin, is widely used as a last-line treatment for multidrug-resistant (MDR) gram-negative bacterial infections in critically ill patients presenting a considerably high mortality rate. However, nephrotoxicity is considered to be a critical adverse effect that limits CMS's clinical use. Alpha-lipoic acid (ALA) is a strong antioxidant that is effective in preventing nephrotoxicity in many models. The aim of this study was to investigate ALA's ability to protect against nephrotoxicity induced by colistin in rats. Male Wistar albino rats were randomly divided into four groups. Group 1 was the control group (Control; n = 6), in which isotonic saline was administered to the rats. Group 2 was the ALA group (ALA; n = 6) in which rats received 100 mg/kg ALA. Groups 3 was the CMS (CMS; n = 7) in which 450.000 IU/kg/day of CMS was administered to the rats. Groups 4 was the CMS + ALA group (n = 6), in which rats were injected with 100 mg/kg of ALA 30 min before administration of CMS. All injections were performed intraperitoneally at 1, 4, 7, and 10 days. Urine was collected by using a metabolic cage for 24 h after each administration. The rats were euthanized under ether anesthesia after 24 h of the last administration. Blood and kidney samples then were collected for histological and biochemical analysis. ALA pretreatment could reverse the effects of colistin-induced nephrotoxicity, partly through its suppressing effect on Nox4 and caspase-3, which in turn results in its antioxidant and antiapoptotic effect. Therefore, ALA may be an effective strategy for the management of colistin nephrotoxicity.